Eksplorasi Pengalaman Menginap Mewah: Analisis Reservasi Hotel Meliá Bali pada The Level Presidential Suite dengan Pemandangan Taman - Winata, Aldo; Pitanatri, Made Uttari (Program Studi Administrasi Perhotelan, 2024)
This research presents an in-depth exploration of the luxury stay experience through analysis of Hotel Meliá Bali reservations, especially at The Level Presidential Suite with stunning garden views. With an area of 176 square meters, this suite offers a magnificent space involving a double bed and two single beds. The space is split over two floors, with a warm colored lounge and wooden floors downstairs, and a luxurious bedroom with a king four-poster bed upstairs. Exclusive facilities, such as shower and bath, private kitchen, private check-in, and flat-screen TV service with high-speed Wifi, provide an unforgettable touch of comfort. Additional privileges include exclusive access to The Level Lounge, private pool and beach area. This research uses a descriptive approach to analyze the experiences of guests staying in this suite. With keywords such as